Anti-cancer activity elucidation of geissolosimine as an MDM2-p53 interaction inhibitor: An in-silico study - Md. Al-Amin; Rehnuma Tanjin; Md. Rasul Karim; Jannatul Mawa Etee; Ayesha Siddika; Nafisa Akter; Md. Helal Uddin; Ratul Mahmud; Tasfia Saffat; Md. Faruk Hossen; Samira Idris Mowlee; Elmu Kabir Rafa; et al. (PLoS ONE, 2025)
For cancer treatment, Inhibition of murine double minute (MDM2) & p53 interaction is considered an attractive therapeutic approach. In this study, we performed an integrated virtual screening (i.e., QSAR, structural similarity, molecular docking, and molecular dynamic simulation) on the in-house building alkaloids library. Geissolosimine (i.e., an indole alkaloid) was predicted as a potential inhibitor for MDM2-p53 interaction. The predicted pIC50 value of Geissolosimine, was 7.013 M. Moreover, Geissolosimine showed 0.62% structural similarity to ‘SAR405838’ (i.e., a clinical trial inhibitor for MDM2-p53 interaction inhibition); and a docking score of -10.9 kcal/mol that was higher than the ‘SAR405838’.100 ns molecular dynamics simulation (MDS) was performed to validate the docking result and it exhibited better binding stability to MDM2. The pharmacokinetic & drug-likeness analysis suggested that Geissolosimine had potential to be a drug-like compound. However, in vitro & in vivo assays will be required to validate this study.